Digital competence in the Norwegian teacher education and schools - Krumsvik, Rune Johan (Högre utbildning, 2011)
<span style="font-size: 12.0pt; mso-bidi-font-size: 10.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: NO-BOK; mso-bidi-language: AR-SA;" lang="EN-GB">The purpose of this article is to examine how policy documents in Norway the last ten years have interpreted ICT and digital competence in teacher education and in school. Norway implemented in 2006 a new national curriculum which increased the status of digital competence to be the fifth basic skill in the Norwegian elementary school (stage 1-13). This was a historic event and never before has digital competence achieved such status in curricula, neither nationally nor internationally. The same has newly happened with the new General Plan for Teacher Education where digital competence has become the fifth basic skill in all subjects. However, both teacher educators and teachers lack sufficient digital competence to fulfil these ambiguous policy goals and therefore the article suggest how a model of digital competence can bridge some of the gap between the intentions in the policy documents and the teachers/teacher educators’ practise. At the same time the article attempts to elaborate our perception of the concept digital competence in an educational discourse and how one can define digital competence in light of a Scandinavian educational perspective. The research question in this article is: how can digital competence be defined and what are the foundations of digital competence in teacher education and schools in light of the policy documents in Norway?